Implementing Collaborative Learning Method in Speaking Class: Students’ View - Silvia Unasanta Br Sembiring; Dian Novita Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Collaborative learning method is a popular method implemented in classes due to collaborative learning can motivate the students to more active in class, explore the lesson as a team and achieve a task together. This study aims at finding out how collaborative learning method in a speaking class from students' views of EFL students, and what are the challenges when collaborative learning method implemented in English class for students. This study was completed using a survey study method and was conducted with 100 EFL students at SMA Panjura Malang. To explore the students' view on the use of collaborative learning method in speaking class, all 100 students were asked to fill out a questionnaire. The data were then analyzed by thematic analysis. By implementing collaborative learning, the students could do the task together and they agree that collaborative learning better than individual for their speaking learning activities.